Self Esteem and Impulsive Buying: Study on Online Shopping Behavior - Rofiq, Maily Qisti; Setyorini, Th. Dewi; Lekahena, Femmy (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
The lifestyle’s demand among college students raise their desire to do online purchase on product which not suitable with their needs. The aim of this research is to empirically ascertain the relationship between impulsive buying and self-esteem in students who shop online at University X Yogyakarta. The subjects in this study were 75 students from the Faculty of Psychology, University X Yogyakarta who were in the 2019 to 2022 class, ages 18 to 21 years, female gender, and had made online purchases in several e-commerce applications. Data collection was carried out using a self-esteem scale and an impulsive buying behavior scale. Data was analuysed by the product moment correlation technique. Based on the resultd of the correlation test, it was abtained that the correlation coefficient of self-esteem with impulsive buying behavior was -0.477 with sig. p = 0.000 (p<0.01). This research can be used as evaluation material for students to be more accepting of what they have and plan before making a purchase so as to reduce the level of impulsive buying behavior.Tuntutan gaya hidup di kalangan mahasiswa memunculkan keinginan mahasiswa melakukan pembelian online yang tidak sesuai dengan kebutuhan mereka. Tujuan penelitian ini adalah untuk memastikan secara empiris hubungan antara perilaku pembelian impulsif dan self-esteem pada mahasiswi yang berbelanja secara online di Universitas X di Yogyakarta. Subjek pada penelitian ini sebanyak 75 mahasiswa dari Fakultas Psikologi yang berada di angkatan 2019 hingga 2022, usia 18 hingga 21 tahun, jenis  kelamin perempuan, serta pernah melakukan pembelian online di beberapa aplikasi e-commerce. Pengambilan data dilakukan dengan menggunakan skala self esteem dan skala perilaku pembelian impulsif. Analisis data  menggunakan teknik korelasi product moment. Berdasarkan hasil uji korelasi diperoleh koefisien korelasi dari self esteem dengan perilaku pembelian impulsif sebesar -0,477 dengan sig. p = 0,000 (p<0,01). Penelitian ini dapat dijadikan sebagai bahan evaluasi bagi mahasiswa untuk dapat lebih menerima dirinya dengan apa yang telah dimiliki dan melakukan perencanaan sebelum melakukan pembelian sehingga dapat menurunkan tingkat perilaku pembelian impulsifnya.